2009
DOI: 10.1007/s11689-009-9026-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental learning impairments in a rodent model of nodular heterotopia

Abstract: Developmental malformations of neocortex—including microgyria, ectopias, and periventricular nodular heterotopia (PNH)—have been associated with language learning impairments in humans. Studies also show that developmental language impairments are frequently associated with deficits in processing rapid acoustic stimuli, and rodent models have linked cortical developmental disruption (microgyria, ectopia) with rapid auditory processing deficits. We sought to extend this neurodevelopmental model to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Thus, as previously reported, improved behavioral performance in HI injured animals is likely to interact with, the age of assessment, treatment dose, injury and test timing and the cognitive/sensory domain that is examined (Threlkeld, McClure et al 2006, Threlkeld, Hill et al 2012, Threlkeld, Gaudet et al 2014, Gaudet, Lim et al 2016). It is important to emphasize that these interacting factors have been reported in many other rodent models of neurodevelopmental disorders including those with neocortical microgiria, heterotopia and knockdown of candidate genes specific to human learning impairments (Threlkeld, McClure et al 2007, Threlkeld, Hill et al 2009, Threlkeld, Hill et al 2009). These complexities are further supported by the present results showing profound differences in tone-order discrimination for adult rats that were treated with IAIPs as neonates at the time of Hypoxia-ischemia exposure, as compared to untreated subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as previously reported, improved behavioral performance in HI injured animals is likely to interact with, the age of assessment, treatment dose, injury and test timing and the cognitive/sensory domain that is examined (Threlkeld, McClure et al 2006, Threlkeld, Hill et al 2012, Threlkeld, Gaudet et al 2014, Gaudet, Lim et al 2016). It is important to emphasize that these interacting factors have been reported in many other rodent models of neurodevelopmental disorders including those with neocortical microgiria, heterotopia and knockdown of candidate genes specific to human learning impairments (Threlkeld, McClure et al 2007, Threlkeld, Hill et al 2009, Threlkeld, Hill et al 2009). These complexities are further supported by the present results showing profound differences in tone-order discrimination for adult rats that were treated with IAIPs as neonates at the time of Hypoxia-ischemia exposure, as compared to untreated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that as the demand of a specific task increases, the deficits become more apparent in juvenile and adult rodents exposed to neonatal HI brain injury relative to sham subjects, irrespective of the quantity of HI injury (Threlkeld, Hill et al 2009, Gaudet, Lim et al 2016). Therefore, given the above considerations, the present study sought to determine the efficacy of IAIPs to improve auditory processing using a modified acoustic startle paradigm with increasing levels of cue complexity (i.e., task demand; simple normal single tone detection, gap detection in white noise and complex oddball tone-pair discrimination) in adult rats exposed to neonatal HI.…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in RAP have been suggested to be predictive of such language impairments in these and other populations [14,15,16,17,18]. Tests of RAP have been successfully developed for use in animal models, and such tasks reveal deficits in rodents with induced brain injuries including HI [22,23,24,25,26,37,38], microgyria and/or ectopia [27,28,29,30,31,32,33,34,35], and prenatal teratogenic exposure [36]. However, these models have never shown comparable deficits in female rodents with early injury [30,31,37,38], consistent with clinical data indicating poorer prognosis for male infants suffering HI as compared to matched females.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, indices of rapid auditory processing (RAP) are consistently impaired in populations with language disability, possibly reflecting anomalies in underlying neural ‘machinery’ critical to language development and processing [[15], [19], [20]; for a review, see [21]]. Importantly, RAP can be measured in animal models, and is consistently impaired in male rodents with induced neonatal brain injuries including perinatal HI [22,23,24,25,26], microgyria and ectopia (small perinatally occurring cortical malformations) [27,28,29,30,31,32,33,34,35], and prenatal teratogenic exposure [36]. Interestingly, female rodents fail to show significant behavioral RAP deficits associated with any comparable perinatal brain injury, including HI [30,31,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…For example, rodent studies have examined disruption of normal cortical development through injury (focal freeze lesion; [14]–[17]), embryonic exposure to teratogens [18], and/or genetic factors (either intrinsic or genetically manipulated; [19][21]). Results show that differing types of neuropathology can lead to different types of anomalous behavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%